Crowdsourcing platform for healthcare: cleft lip and cleft palate case studies - Krit Khwanngern (2020)
© Springer Nature Switzerland AG 2020. In this paper, we present a design for the healthcare system which extends the existing medical cloud services in order to overcome the challenges of searching the new patients and following-up the existing patients. We explain that the existing platforms are working on different healthcare levels, with separate groups of users, and on different devices. We introduce additional design of the system which acts as a bridge between these platforms. Utilizing the aspect of crowdsourcing and online data sharing, the system can benefits contributors by significantly reduce the amount of time, cost and workload of all users in the system.